Induction System with Deformation Control Unit for Local Softening of Hot-Stamped Parts - Kim, Dong Kyu; Woo, Young Yun; Sim, Woo Jeong; Kim, Won Hyuk; Kim, Ji Hoon; Moon, Young Hoon (International journal of automotive technology, 2021)
Hot-stamped parts in a fully martensitic state exhibit very low ductility levels prior to failure, which limits their use in certain components. In the case of B-pillars, which may undergo impact loading, it could be desirable to create part zones with softer and more ductile microstructures. Local softening by means of an induction heating system is one of the methods of tailoring the properties for increasing overall energy absorption while minimizing additional manufacturing facilities. Through selective heating of the hardened zone, it is possible to form zones with very high strength and regions of reduced strength but increased ductility, resulting in a part with tailored mechanical properties. As local softening by induction heating is affected by thermomechanical properties, thermal deformation due to local heating is inevitably induced. Therefore, in this study, a local induction heating system combined with a deformation control unit is developed to minimize thermal deformation induced by local softening. The effectiveness of the system performance is strongly confirmed by the on-line application in the production line, and part qualities are significantly improved.